Barriers and facilitators of research utilization among nurses working in teaching hospitals in Tabriz - L Vali Zadeh; V Zaman Zadeh; A Fathi Azar; A Safaeian (Tehran University of Medical Sciences, 2002)
This research is a descriptive study in order to assess barriers and facilitators of research utilization among nurses working in teaching hospitals in Tabriz, year 2001. The aim is to identify causes of low extent of utilization and also to assess barriers and facilitators of researches. This study was conducted upon 304 nurses working in 12 teaching hospitals of Tabriz, which were selected by random sampling. Instrument used for study was questionnaire. Data were analyzed using SPSS (10). The results of this study showed that three major barriers for research utilization included: 1) inadequate facilities for implementation, 2) Physicians will not cooperate with implementation and 3) the nurses do not have sufficient time to read researches. Facilitators which nurses suggested, emphasized on the role of education in enhancing their knowledge and skills of research evaluation.